Contribuições da teoria de Joseph Raz para a consolidação de uma teoria dos precedentes constitucionais: a ideia de discricionariedade forte e o contraste entre precedentes ordinários e precedentes constitucionais - Igor de Carvalho Enriquez (2018)
Throughout his work, Joseph Raz seeks to design a project of political and moral philosophy that underpins a comprehensive and complete legal theory. It can be divided into five major parts (theories of practical rationality, morality, authority, law, and adjudication) in which answers are established to problems long debated in the philosophical circles. Although critics claim the lack of internal coherence between these five fundamental parts of his work, it is intended in this thesis to demonstrate that it is present and relevant, although it is not evident at first. His great merit is to establish parameters for the compatibility between an exclusive positivism and a normative theory, which, in general terms, is a defense of the compatibility between, on the one hand, the source thesis (according to which the law is the product of and the theory of moral adjudication) added with the separation thesis (according to which there is a necessary separation of law and morality) and, on the other, a theory of moral adjudication (according to which the court must decide based on moral parameters shared by its community, although it is not totally limited to them).This PhD thesis seeks to face the criticisms that question both the compatibility of several of its parts with each other and the factual plausibility of parts of its work compared to the reality of applied law. For this, it is shown how there was a conscious change of the initial phase of the writings of Raz, where the intention was to treat law as a sum of practical reasons conceived in the form of directives aiming to obtain social coordination, for a second moment, in the his work evolves to an attempt to establish a theory of law coupled with a theory of adjudication in which morality becomes the basis for making judicial decisions, both in filling gaps and in the constitutional framework. It is argued here, therefore, that answers can help clarify pertinent points of constitutional theory by assisting both in the implementation of a procedural political project and in treating constitutional decisions as what they are in fact: political decisions taken by courts with power for that.